Hydrophobic heat-conducting self-repairing composite coating and preparation method thereof
By applying hydrophobic and thermal self-healing coating on power equipment, the problem of traditional anti-condensation measures being unsatisfactory in extreme environments is solved, and the combination of thermal conductivity, self-healing and hydrophobic functions is achieved, extending the service life of the equipment and reducing costs.
Patent Information
- Application Number
- CN202411615462.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-03-04
AI Technical Summary
Traditional anti-condensation measures are not ideal in extremely harsh environments and are costly, making it difficult to meet the requirements of stable operation of the power system.
Using a preparation method of a hydrophobic and thermally conductive self-healing coating, a thermally conductive filler and polyethylene glycol are dispersed in an organic solvent and dripped into an aqueous epoxy resin solution to form a thermally conductive coating solution. At the same time, self-healing microcapsules are prepared and added to the fluoropolymer solution with silica to form a self-healing hydrophobic coating solution, and the distribution of microcapsules is controlled in a directionally through electric or magnetic field-induced deposition technology.
It realizes that the thermal conductivity and self-repair performance of the coating can be improved without affecting the hydrophobic performance, extend the service life of the equipment, and reduce operating costs.
Smart Images

Figure CN119549375A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of paint coatings, and in particular to a method for preparing a hydrophobic, heat-conductive, self-repairing coating. Background Art
[0002] In the field of traditional distribution networks, condensation prevention has always been one of the difficult problems in the power sector. In extremely harsh environments, traditional distribution network equipment uses desiccants, silicone rubber and other materials to absorb moisture in the cabinet, or installs dehumidifiers and condensers to prevent condensation. This approach not only has unsatisfactory results, but also increases operating costs. In addition, the number of rural and urban substations is also increasing. Traditional anti-condensation measures are obviously difficult to meet the requirements of stable operation of the power system. In order to improve the anti-condensation effect, the current practice is to apply a hydrophobic coating on the surface of the workpiece. However, the existing coating is prone to aging of the hydrophobic layer due to the large amount of heat generated during the operation of the power equipment, thereby further affecting the hydrophobic performance. In addition, there is also a self-healing agent to repair the aged coating so that the hydrophobic performance is not affected. However, the current commonly used approach has a complex process, uses a large number of raw materials, and is costly.
[0003] Therefore, there is an urgent need to develop a new multifunctional coating for use in power equipment to achieve thermal conductivity, self-healing and hydrophobic functions, thereby extending the service life of the equipment. Summary of the invention
[0004] The object of the present invention is to provide a hydrophobic thermal conductive coating and a preparation method thereof, which has a simple preparation process, simple raw materials and low cost, and can timely conduct the heat generated on the surface of the substrate without affecting the hydrophobic performance, and can self-repair the damaged coating, thereby increasing the service life of the coating.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] A method for preparing a hydrophobic thermally conductive self-repairing coating comprises the following steps:
[0007] S1, ultrasonically dispersing a thermally conductive filler and polyethylene glycol in an organic solvent, dripping the organic solvent into an aqueous epoxy resin solution, stirring at a speed of 500 to 1000 rpm for 30 to 60 minutes, to obtain a thermally conductive coating liquid, wherein the mass fraction of the thermally conductive filler in the thermally conductive coating liquid is 10 to 30%;
[0008] S2, dissolving polysiloxane and fluorine-containing monomers in ethyl acetate by stirring to form liquid A; dissolving polyethylene glycol in deionized water to form liquid B, adding the liquid A dropwise to the liquid B under low-speed stirring at room temperature, continuing stirring for 20-30 minutes after all the additions are complete, gradually raising the temperature to 40° C., maintaining the speed constant, continuing stirring for 2-3 hours, and then centrifugally filtering and drying to obtain self-healing microcapsules;
[0009] S3, adding the self-healing microcapsules and silica prepared in step S2 to a fluoropolymer solution and / or a hydrophobic resin solution and ultrasonically dispersing them for 30 to 60 minutes to prepare a self-healing hydrophobic coating liquid, wherein the amount of the self-healing microcapsules added is 10 to 20% of the mass of the fluoropolymer solution and / or the hydrophobic resin solution, and the amount of silica added is 1 to 5% of the mass of the fluoropolymer solution and / or the hydrophobic resin solution; when preparing the coating, the distribution of the microcapsules in the coating is directionally controlled by electric field or magnetic field induced deposition technology to ensure that the microcapsules are more densely distributed in the stress concentration area to enhance the probability of rupture.
[0010] S4, uniformly spraying or spin-coating the thermal conductive coating liquid obtained in step S1 on the surface of the metal substrate, and UV curing for 10 to 20 minutes to obtain a thermal conductive coating;
[0011] S5, continue to evenly spray or spin-coat the surface of the thermal conductive coating prepared in step S4 with the self-repairing hydrophobic coating liquid prepared in step S3, and UV cure for 10 to 20 minutes to obtain a hydrophobic thermal conductive self-repairing coating.
[0012] As the preferred technical solution:
[0013] Optionally, in step S1, the mass ratio of the thermal conductive filler to the polyethylene glycol is 1:1, the total amount of the thermal conductive filler and the polyethylene glycol added accounts for 30-50% of the organic solvent, the thermal conductive filler is a metal oxide and / or a carbon-based material; the organic solvent is ethanol, isopropanol, benzyl alcohol or ethylene glycol; the ultrasonic dispersion time is 30-40 minutes. The polyethylene glycol is a low molecular weight polyethylene glycol, specifically PEG-400.
[0014] Optionally, the thermal conductive filler is a mixture of one or more of flaky aluminum oxide nanofibers, flaky zinc oxide nanofibers, graphene fibers or carbon nanotubes, and the length of the flaky aluminum oxide nanofibers and flaky zinc oxide nanofibers is 10 to 30 μm.
[0015] Optionally, in step S2, the mass ratio of polysiloxane to fluorine-containing monomer in the liquid A is 1:(1-2), the concentration of the liquid A is 5-20wt%, and the concentration of the liquid B is 0.5-2wt%; the volume ratio of the liquid A to the liquid B is 1:(5-10); the dripping rate of the liquid A into the liquid B is 0.1-0.5mL / min; the polyethylene glycol is a low molecular weight polyethylene glycol, specifically PEG-400.
[0016] The low-speed stirring speed is 300-400rpm; the gradual heating is carried out in the form of water bath heating, and the heating rate is 0.5-0.8°C / min; the centrifugal filtration and drying refers to centrifuging at a speed of 3000-3500rpm for 10-20min in a centrifuge at room temperature, then filtration and vacuum drying for 10-12h, and before vacuum drying, repeatedly washing with deionized water for 3-5 times, each time for 3-5min, and adding a small amount of ethanol for the last washing;
[0017] The capsule wall of the self-repairing microcapsule has a thickness of 200-300 nm, the capsule shell is made of polysiloxane and fluorine-containing monomers, and the capsule core is made of polyethylene glycol.
[0018] Optionally, in step S2, a crosslinking agent and a catalyst are added to ethyl acetate while adding the polysiloxane and the fluorine-containing monomer. The amount of the crosslinking agent added is 1-2 wt % of the polysiloxane, and the amount of the catalyst added is 0.5-1 wt % of the polysiloxane.
[0019] Optionally, the polysiloxane is polydimethylsiloxane or polyvinylsiloxane, the fluorine-containing monomer is tetrafluoroethylene, chlorotrifluoroethylene, vinyl fluoride, vinylidene fluoride or hexafluoroacrylate; the crosslinking agent is methyltriethoxysilane, and the catalyst is a platinum-based catalyst.
[0020] Optionally, in step S3, before adding the self-healing microcapsules and silica to the fluoropolymer solution or the hydrophobic resin solution, the self-healing microcapsules and silica are ultrasonically dispersed in ethanol or deionized water, respectively, and the volume content of the ethanol or deionized water is 60-70% of the self-healing microcapsules and the silica.
[0021] Optionally, the fluorine-containing polymer is polytetrafluoroethylene, polyvinylidene fluoride, fluorine-containing polysiloxane or perfluoroalkyl acrylate copolymer; and the hydrophobic resin is silicone resin, fluorocarbon resin, epoxy resin or polyurethane resin.
[0022] Optionally, in steps S4 and S5, the coating thickness is controlled to be 10 to 50 μm, and the UV curing condition is to use ultraviolet rays with a wavelength of 365 nm and an energy of 5 to 10 J / cm2 for curing.
[0023] The present invention also provides a hydrophobic, thermally conductive, self-repairing coating prepared by the preparation method described above.
[0024] Invention mechanism:
[0025] The present invention prepares a thermally conductive coating liquid and a self-repairing coating liquid, and sprays or spin-coats them on the surface of a metal substrate to form a coating, thereby combining thermal conductivity, self-repairing properties and hydrophobic properties to obtain a coating with excellent performance.
[0026] By ultrasonically dispersing the thermally conductive filler and polyethylene glycol in an organic solvent and then dropping the mixture into an aqueous epoxy resin solution, the thermally conductive filler can be uniformly dispersed in the aqueous epoxy resin under the combined action of polyethylene glycol and ultrasonic dispersion. The polyethylene glycol can effectively coat the surface of the thermally conductive filler, reducing the van der Waals force between particles, thereby preventing the conductive filler from agglomerating in the aqueous epoxy resin solution. The thermally conductive filler forms a uniform thermal conductive channel in the aqueous epoxy resin matrix, thereby having thermal conductivity.
[0027] By using polysiloxane and fluorine-containing monomers as the capsule wall of the self-healing microcapsule and polyethylene glycol as the core material, the prepared self-healing microcapsules have excellent performance. Polysiloxane has excellent thermal stability, which can protect the repair agent in the microcapsule from being affected in a high temperature environment, and also improves the durability of the microcapsule itself. When cracks appear in the material, the cracks extend to the surface of the microcapsule and tear the capsule wall. The rupture of the polysiloxane capsule wall can prompt the repair agent polyethylene glycol to flow out and solidify at the crack, thereby repairing the crack.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] The preparation method of the present invention is simple. It uses simple raw materials to combine the thermal conductivity, self-repairing and hydrophobic functions. The double-layer coating structure design improves the thermal conductivity and self-repairing properties of the coating while ensuring the mechanical properties and hydrophobic effects, and meets the requirements of power equipment for the coating's weather resistance, UV aging resistance and other properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1 It is a schematic flow chart of the method for preparing the hydrophobic thermally conductive self-repairing coating of the present invention. DETAILED DESCRIPTION
[0032] In the following, only some exemplary embodiments are briefly described. As those skilled in the art will appreciate, the described embodiments may be modified in various ways without departing from the spirit or scope of the present invention. Therefore, the drawings and descriptions are considered to be exemplary and non-restrictive in nature.
[0033] The embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0034] The present invention provides a method for preparing a hydrophobic thermally conductive self-repairing coating. Figure 1 As shown, the following steps are included:
[0035] S1, ultrasonically dispersing a thermal conductive filler and polyethylene glycol in a mass ratio of 1:1 in an organic solvent, dripping the mixture into an aqueous epoxy resin solution, and stirring the mixture at a speed of 500 to 1000 rpm for 30 to 60 minutes to obtain a thermal conductive coating liquid;
[0036] The mass fraction of the thermal conductive filler in the thermal conductive coating liquid is 10-30%, the total amount of the thermal conductive filler and the polyethylene glycol added accounts for 30-50% of the organic solvent, the thermal conductive filler is a metal oxide and / or a carbon-based material, specifically a mixture of one or more of flaky aluminum oxide nanofibers, flaky zinc oxide nanofibers, graphene fibers or carbon nanotubes, and the average diameter of the flaky aluminum oxide nanofibers and the flaky zinc oxide nanofibers is 50-80 nm; the organic solvent is ethanol, isopropanol, benzyl alcohol or ethylene glycol, the ultrasonic dispersion time is 30-40 min, the polyethylene glycol is PEG-400, and the drop rate of the thermal conductive filler after ultrasonic dispersion into the aqueous epoxy resin solution is 0.1-0.5 mL / min;
[0037] S2, dissolving polysiloxane and fluorine-containing monomers in ethyl acetate by stirring to form liquid A; dissolving polyethylene glycol in deionized water to form liquid B, adding the liquid A dropwise to the liquid B under low-speed stirring at room temperature, continuing stirring for 20-30 minutes after all the additions are complete, gradually raising the temperature to 40° C., maintaining the speed constant, continuing stirring for 2-3 hours, and then centrifugally filtering and drying to obtain self-healing microcapsules;
[0038] The mass ratio of polysiloxane to fluorine-containing monomer in liquid A is 1:(1-2), the concentration of liquid A is 5-20wt%, and the concentration of liquid B is 0.5-2wt%; the volume ratio of liquid A to liquid B is 1:(5-10); the dripping rate of liquid A to liquid B is 0.1-0.5mL / min, and polyethylene glycol is PEG-400;
[0039] The speed of low-speed stirring is 300-400 rpm; the temperature is gradually increased in the form of water bath heating, and the heating rate is 0.5-0.8°C / min; centrifuge at 3000-3500 rpm for 10-20 minutes at room temperature in a centrifuge, then filter and vacuum dry for 10-12 hours, and wash repeatedly with deionized water for 3-5 times, each time for 3-5 minutes before vacuum drying, and add a small amount of ethanol for the last wash;
[0040] The thickness of the capsule wall of the self-repairing microcapsule is 200-300 nm, the capsule shell is made of polysiloxane and fluorine-containing monomers, the capsule core is made of polyethylene glycol, and the polysiloxane is a low molecular weight polysiloxane, specifically disiloxane, trisiloxane or tetrasiloxane;
[0041] When polysiloxane and fluorine-containing monomers are added to ethyl acetate, a crosslinking agent and a catalyst are also added. The amount of the crosslinking agent added is 1-2wt% of the polysiloxane, and the amount of the catalyst added is 0.5-1wt% of the polysiloxane. The polysiloxane is specifically polydimethylsiloxane or polyvinylsiloxane, and the fluorine-containing monomer is tetrafluoroethylene, trifluorochloroethylene, vinyl fluoride, vinylidene fluoride or hexafluoroacrylate; the crosslinking agent is methyltriethoxysilane, and the catalyst is a platinum-based catalyst.
[0042] S3, first ultrasonically dispersing the self-repairing microcapsules and silica obtained in step S2 into ethanol or deionized water, respectively, and then adding them into a fluorine-containing polymer solution and / or a hydrophobic resin solution and ultrasonically dispersing them for 30 to 60 minutes to obtain a self-repairing hydrophobic coating liquid;
[0043] The volume content of ethanol or deionized water is 60-70% of the self-repairing microcapsules and silica, the amount of self-repairing microcapsules added is 10-20% of the mass of the fluoropolymer solution and / or the hydrophobic resin solution, and the amount of silica added is 1-5% of the mass of the fluoropolymer solution and / or the hydrophobic resin solution;
[0044] The fluorine-containing polymer is polytetrafluoroethylene, polyvinylidene fluoride, fluorine-containing polysiloxane or perfluoroalkyl acrylate copolymer; the hydrophobic resin solution is an organic silicone resin solution, a fluorocarbon resin solution, an epoxy resin solution or a polyurethane resin solution, wherein the fluorine-containing polysiloxane can be hexafluorocyclobutyl ether;
[0045] S4, uniformly spraying or spin-coating the thermal conductive coating liquid obtained in step S1 on the surface of the metal substrate, and UV curing for 10 to 20 minutes to obtain a thermal conductive coating, wherein the thickness of the thermal conductive coating is controlled to be 10 to 50 μm, and the UV curing condition is to use ultraviolet rays with a wavelength of 365 nm and an energy of 5 to 10 J / cm2 for curing;
[0046] S5, continue to evenly spray or spin-coat the self-healing hydrophobic coating liquid prepared in step S3 on the surface of the thermal conductive coating prepared in step S4, and UV cure for 10 to 20 minutes to obtain a hydrophobic thermal conductive self-healing coating, wherein the thickness of the self-healing hydrophobic coating is controlled to be 10 to 50 μm, and the UV curing condition is to use ultraviolet rays with a wavelength of 365 nm and an energy of 5 to 10 J / cm2 for curing.
[0047] The following is a more specific example:
[0048] Example 1
[0049] A method for preparing a hydrophobic thermally conductive self-repairing coating comprises the following steps:
[0050] S1, after ultrasonically dispersing flaky aluminum oxide nanofibers and polyethylene glycol in a mass ratio of 1:1 in ethanol for 30 minutes, dripping the dispersion into an aqueous epoxy resin solution, and stirring the mixture at a speed of 900 rpm for 55 minutes to obtain a thermal conductive coating liquid;
[0051] The ultrasonically dispersed flaky aluminum oxide nanofibers and polyethylene glycol were dripped into the aqueous epoxy resin solution at a dropping rate of 0.1 mL / min, the mass fraction of the flaky aluminum oxide nanofibers in the thermal conductive coating solution was 10%, the total amount of the flaky aluminum oxide nanofibers and polyethylene glycol added accounted for 50% of ethanol, and the average length of the flaky aluminum oxide nanofibers was 10 μm;
[0052] S2, polydimethylsiloxane and tetrafluoroethylene in a mass ratio of 1:1.5 are stirred and dissolved in ethyl acetate to form a liquid A with a concentration of 15wt%; polyethylene glycol is dissolved in deionized water to form a liquid B with a concentration of 2wt%, and liquid A is added dropwise to liquid B at a rate of 0.25mL / min under stirring at 300rpm at room temperature. After all the additions are completed, stirring is continued for 30min, and the temperature is gradually increased to 40°C at a heating rate of 0.5°C / min in a water bath, and the speed is kept constant and stirring is continued for 2h. Then, the mixture is centrifuged at 3000rpm at room temperature for 10min, filtered and vacuum dried for 11h, and self-repairing microcapsules are obtained after centrifugal filtration and drying, wherein the volume ratio of liquid A to liquid B is 1:5; the thickness of the capsule wall of the obtained self-repairing microcapsules is 200-300nm, and the material is polydimethylsiloxane and tetrafluoroethylene, and the material of the capsule core is polyethylene glycol;
[0053] S3, first ultrasonically dispersing the self-repairing microcapsules and silicon dioxide obtained in step S2 into deionized water respectively, and then adding them into a polytetrafluoroethylene solution and ultrasonically dispersing them for 30 minutes to obtain a self-repairing hydrophobic coating liquid;
[0054] The volume content of deionized water is 60% of the self-repairing microcapsules and silica, the amount of self-repairing microcapsules added is 10% of the mass of the polytetrafluoroethylene solution, and the amount of silica added is 2.7% of the mass of the polytetrafluoroethylene solution;
[0055] S4, spraying or spin-coating the thermal conductive coating liquid obtained in step S1 uniformly on the surface of the metal substrate, and UV curing for 10 minutes to obtain a thermal conductive coating, wherein the thickness of the thermal conductive coating is controlled to be 30 μm, and the UV curing condition is to use ultraviolet rays with a wavelength of 365 nm and an energy of 5 to 10 J / cm2 for curing;
[0056] S5, continue to evenly spray or spin-coat the self-healing hydrophobic coating liquid prepared in step S3 on the surface of the thermal conductive coating prepared in step S4, and UV cure for 20 minutes to obtain a hydrophobic thermal conductive self-healing coating, wherein the thickness of the self-healing hydrophobic coating is controlled to be 30 μm, and the UV curing condition is to use ultraviolet rays with a wavelength of 365 nm and an energy of 5 to 10 J / cm2 for curing.
[0057] Example 2
[0058] A method for preparing a hydrophobic thermally conductive self-repairing coating comprises the following steps:
[0059] S1, after ultrasonically dispersing flaky zinc oxide nanofibers and polyethylene glycol in a mass ratio of 1:1 in isopropanol for 35 minutes, dripping the dispersion into an aqueous epoxy resin solution, and stirring the mixture at a speed of 500 rpm for 60 minutes to obtain a thermal conductive coating liquid;
[0060] The ultrasonically dispersed flaky zinc oxide nanofibers and polyethylene glycol are dripped into the aqueous epoxy resin solution at a dropping rate of 0.5 mL / min, the mass fraction of the flaky zinc oxide nanofibers in the thermal conductive coating solution is 10%, the total amount of the flaky zinc oxide nanofibers and polyethylene glycol added accounts for 50% of the isopropanol, and the average length of the flaky zinc oxide nanofibers is 20 μm;
[0061] S2, dissolving polydimethylsiloxane and tetrafluoroethylene in a mass ratio of 1:1 in ethyl acetate by stirring to form a liquid A with a concentration of 5wt%; dissolving polyethylene glycol in deionized water to form a liquid B with a concentration of 1wt%, dripping the liquid A into the liquid B at a rate of 0.3mL / min under low-speed stirring at 300rpm at room temperature, continuing stirring for 30min after all the dripping is completed, gradually heating to 40°C at a heating rate of 0.8°C / min in a water bath, keeping the speed unchanged, stirring for 2h, centrifuging at 3500rpm at room temperature in a centrifuge for 10min, filtering and vacuum drying for 11h, and obtaining self-repairing microcapsules after centrifugal filtration and drying, wherein the volume ratio of liquid A to liquid B is 1:8; the capsule wall thickness of the self-repairing microcapsules is 200-300nm, and the material is polydimethylsiloxane and tetrafluoroethylene, and the material of the capsule core is polyethylene glycol;
[0062] S3, first ultrasonically dispersing the self-repairing microcapsules and silicon dioxide obtained in step S2 into ethanol respectively, and then adding them into a mixed solution of polyvinylidene fluoride solution and silicone resin solution in a mass ratio of 1:1 and ultrasonically dispersing them for 30 minutes to obtain a self-repairing hydrophobic coating liquid;
[0063] The volume content of ethanol is 60% of the self-repairing microcapsules and silicon dioxide, the amount of self-repairing microcapsules added is 20% of the mass of the polyvinylidene fluoride solution and the silicone resin solution, and the amount of silicon dioxide added is 3% of the mass of the polyvinylidene fluoride solution and the silicone resin solution;
[0064] S4, spraying or spin-coating the thermal conductive coating liquid obtained in step S1 uniformly on the surface of the metal substrate, and UV curing for 10 minutes to obtain a thermal conductive coating, wherein the thickness of the thermal conductive coating is controlled to be 50 μm, and the UV curing condition is to use ultraviolet rays with a wavelength of 365 nm and an energy of 5 to 10 J / cm2 for curing;
[0065] S5, continue to evenly spray or spin-coat the self-healing hydrophobic coating liquid prepared in step S3 on the surface of the thermal conductive coating prepared in step S4, and UV cure for 12 minutes to obtain a hydrophobic thermal conductive self-healing coating, wherein the thickness of the self-healing hydrophobic coating is controlled to be 44 μm, and the UV curing conditions are to use ultraviolet rays with a wavelength of 365 nm and an energy of 5 to 10 J / cm2 for curing.
[0066] Example 3
[0067] A method for preparing a hydrophobic thermally conductive self-repairing coating comprises the following steps:
[0068] S1, after ultrasonically dispersing graphene fibers and polyethylene glycol in a mass ratio of 1:1 in benzyl alcohol for 40 minutes, dripping the dispersed graphene fibers into an aqueous epoxy resin solution, and stirring the solution at a speed of 800 rpm for 30 minutes to obtain a thermal conductive coating liquid;
[0069] The drop rate of the ultrasonically dispersed graphene fibers and polyethylene glycol dropped into the aqueous epoxy resin solution was 0.3 mL / min, the mass fraction of the graphene fibers in the thermal conductive coating solution was 22%, the total amount of graphene fibers and polyethylene glycol added accounted for 35% of benzyl alcohol, and the average length of the graphene fibers was 30 μm.
[0070] S2, polyvinyl siloxane and chlorotrifluoroethylene in a mass ratio of 1:1 are stirred and dissolved in ethyl acetate to form a liquid A with a concentration of 20wt%; polyethylene glycol is dissolved in deionized water to form a liquid B with a concentration of 1wt%, and the liquid A is added dropwise to the liquid B at a rate of 0.3mL / min under low-speed stirring at 400rpm at room temperature. After all the additions are completed, stirring is continued for 20min, and the temperature is gradually increased to 40°C at a heating rate of 0.5°C / min in a water bath, and the speed is kept constant and stirring is continued for 3h. Then, the mixture is centrifuged at a speed of 3500rpm at room temperature for 10min, filtered and vacuum dried for 12h, and self-repairing microcapsules are obtained after centrifugal filtration and drying, wherein the volume ratio of liquid A to liquid B is 1:5; the capsule wall of the self-repairing microcapsule has a thickness of 200-300nm, and the material is polyvinyl siloxane and chlorotrifluoroethylene, and the material of the capsule core is polyethylene glycol;
[0071] S3, first ultrasonically dispersing the self-repairing microcapsules and silicon dioxide obtained in step S2 into deionized water, respectively, and then adding them into a mixed solution of a fluorinated polysiloxane solution and a fluorocarbon resin solution in a mass ratio of 1:2 and ultrasonically dispersing them for 50 minutes to obtain a self-repairing hydrophobic coating liquid;
[0072] The volume content of deionized water is 70% of the self-repairing microcapsules and silica, the amount of self-repairing microcapsules added is 10% of the mass of the mixed solution of the polysiloxane polymer solution and the fluorocarbon resin solution, and the amount of silica added is 4.1% of the mass of the mixed solution of the polysiloxane polymer solution and the fluorocarbon resin solution;
[0073] S4, spraying or spin-coating the thermal conductive coating liquid obtained in step S1 uniformly on the surface of the metal substrate, and UV curing for 10 minutes to obtain a thermal conductive coating, wherein the thickness of the thermal conductive coating is controlled to be 20 μm, and the UV curing condition is to use ultraviolet rays with a wavelength of 365 nm and an energy of 5 to 10 J / cm2 for curing;
[0074] S5, continue to evenly spray or spin-coat the self-healing hydrophobic coating liquid prepared in step S3 on the surface of the thermal conductive coating prepared in step S4, and UV cure for 20 minutes to obtain a hydrophobic thermal conductive self-healing coating, wherein the thickness of the self-healing hydrophobic coating is controlled to be 50 μm, and the UV curing condition is to use ultraviolet rays with a wavelength of 365 nm and an energy of 5 to 10 J / cm2 for curing.
[0075] Example 4
[0076] A method for preparing a hydrophobic thermally conductive self-repairing coating comprises the following steps:
[0077] S1, ultrasonically dispersing carbon nanotubes and polyethylene glycol in a mass ratio of 1:1 in ethylene glycol for 40 minutes, dripping the mixture into an aqueous epoxy resin solution, and stirring the mixture at a speed of 1000 rpm for 40 minutes to obtain a thermally conductive coating liquid;
[0078] The ultrasonically dispersed carbon nanotubes and polyethylene glycol are dripped into the aqueous epoxy resin solution at a dropping rate of 0.5 mL / min, the mass fraction of carbon nanotubes in the thermal conductive coating liquid is 20%, the total amount of carbon nanotubes and polyethylene glycol added accounts for 30% of ethylene glycol, and the carbon nanotubes are multi-walled carbon nanotubes (MWCNTs) with an outer diameter of 50 nm, an inner diameter of 1.5 nm, and an average length of 20 μm;
[0079] S2, dissolving polyvinylsiloxane and vinyl fluoride in a mass ratio of 1:2 in ethyl acetate by stirring to form a liquid A with a concentration of 10wt%; dissolving polyethylene glycol in deionized water to form a liquid B with a concentration of 0.5wt%, dripping the liquid A into the liquid B at a rate of 0.5mL / min under low-speed stirring at 400rpm at room temperature, continuing to stir for 20min after all the dripping is completed, gradually heating to 40°C at a heating rate of 0.7°C / min in a water bath, keeping the speed unchanged, stirring for 3h, centrifuging at 3500rpm at room temperature in a centrifuge for 20min, filtering and vacuum drying for 12h, and obtaining self-repairing microcapsules after centrifugal filtration and drying, wherein the volume ratio of liquid A to liquid B is 1:6; the capsule wall of the self-repairing microcapsules has a thickness of 200-300nm, and the material is polyvinylsiloxane and vinyl fluoride, and the material of the capsule core is polyethylene glycol;
[0080] S3, first ultrasonically dispersing the self-repairing microcapsules and silica obtained in step S2 into ethanol respectively, and then adding them into the perfluoroalkyl acrylate copolymer solution and ultrasonically dispersing them for 30 minutes to obtain a self-repairing hydrophobic coating liquid;
[0081] The volume content of ethanol is 70% of the self-repairing microcapsules and silica, the amount of self-repairing microcapsules added is 10% of the mass of the perfluoroalkyl acrylate copolymer solution, and the amount of silica added is 2% of the mass of the perfluoroalkyl acrylate copolymer solution;
[0082] S4, spraying or spin-coating the thermal conductive coating liquid obtained in step S1 uniformly on the surface of the metal substrate, and UV curing for 20 minutes to obtain a thermal conductive coating, wherein the thickness of the thermal conductive coating is controlled to be 10 μm, and the UV curing condition is to use ultraviolet rays with a wavelength of 365 nm and an energy of 5 to 10 J / cm2 for curing;
[0083] S5, continue to evenly spray or spin-coat the self-healing hydrophobic coating liquid prepared in step S3 on the surface of the thermal conductive coating prepared in step S4, and UV cure for 120 minutes to obtain a hydrophobic thermal conductive self-healing coating, wherein the thickness of the self-healing hydrophobic coating is controlled to be 10 μm, and the UV curing condition is to use ultraviolet rays with a wavelength of 365 nm and an energy of 5 to 10 J / cm2 for curing.
[0084] Example 5
[0085] A method for preparing a hydrophobic thermally conductive self-repairing coating comprises the following steps:
[0086] S1, ultrasonically dispersing a thermal conductive filler and polyethylene glycol in a mass ratio of 1:1 in ethylene glycol for 35 minutes, then dropping the mixture into an aqueous epoxy resin solution, and stirring the mixture at a speed of 1000 rpm for 30 minutes to obtain a thermal conductive coating liquid;
[0087] The thermal conductive filler and polyethylene glycol after ultrasonic dispersion are dripped into the aqueous epoxy resin solution at a dropping rate of 0.1 mL / min, the mass fraction of the thermal conductive filler in the thermal conductive coating liquid is 30%, the total amount of the thermal conductive filler and polyethylene glycol added accounts for 46% of the ethylene glycol, and the thermal conductive filler is a mixture of flaky aluminum oxide nanofibers and flaky zinc oxide nanofibers (molar ratio of 1:1), with an average diameter of 10 nm;
[0088] S2, polyvinyl siloxane and vinylidene fluoride in a mass ratio of 1:2 are stirred and dissolved in ethyl acetate to form a liquid A with a concentration of 20wt%; polyethylene glycol is dissolved in deionized water to form a liquid B with a concentration of 1.5wt%, and the liquid A is added dropwise to the liquid B at a rate of 0.1mL / min under low-speed stirring at 300rpm at room temperature. After all the additions are completed, stirring is continued for 20min, and the temperature is gradually increased to 40°C at a heating rate of 0.7°C / min in a water bath, and the speed is kept constant and stirring is continued for 2h. Then, the mixture is centrifuged at a speed of 3500rpm at room temperature in a centrifuge for 20min, filtered and vacuum dried for 10h, and self-repairing microcapsules are obtained after centrifugal filtration and drying, wherein the volume ratio of liquid A to liquid B is 1:10; the capsule wall of the self-repairing microcapsule has a thickness of 200-300nm, and the material is polyvinyl siloxane and vinylidene fluoride, and the material of the capsule core is polyethylene glycol;
[0089] S3, first ultrasonically dispersing the self-repairing microcapsules and silicon dioxide obtained in step S2 into ethanol respectively, and then adding them into the organic silicone resin solution and ultrasonically dispersing them for 60 minutes to obtain a self-repairing hydrophobic coating liquid;
[0090] The volume content of ethanol or deionized water is 60% of the self-repairing microcapsules and silicon dioxide, the amount of self-repairing microcapsules added is 20% of the mass of the silicone resin solution, and the amount of silicon dioxide added is 1.3% of the mass of the silicone resin solution;
[0091] S4, spraying or spin-coating the thermal conductive coating liquid obtained in step S1 uniformly on the surface of the metal substrate, and UV curing for 20 minutes to obtain a thermal conductive coating, wherein the thickness of the thermal conductive coating is controlled to be 20 μm, and the UV curing condition is to use ultraviolet rays with a wavelength of 365 nm and an energy of 5 to 10 J / cm2 for curing;
[0092] S5, continue to evenly spray or spin-coat the self-healing hydrophobic coating liquid prepared in step S3 on the surface of the thermal conductive coating prepared in step S4, and UV cure for 15 minutes to obtain a hydrophobic thermal conductive self-healing coating, wherein the thickness of the self-healing hydrophobic coating is controlled to be 30 μm, and the UV curing conditions are to use ultraviolet rays with a wavelength of 365 nm and an energy of 5 to 10 J / cm2 for curing.
[0093] Example 6
[0094] A method for preparing a hydrophobic thermally conductive self-repairing coating comprises the following steps:
[0095] S1, ultrasonically dispersing a thermal conductive filler and polyethylene glycol in a mass ratio of 1:1 in ethanol for 30 minutes, dripping the dispersed polymer into an aqueous epoxy resin solution, and stirring the mixture at a speed of 600 rpm for 45 minutes to obtain a thermal conductive coating liquid;
[0096] The thermal conductive filler and polyethylene glycol after ultrasonic dispersion are dripped into the aqueous epoxy resin solution at a dropping rate of 0.5 mL / min, the mass fraction of the thermal conductive filler in the thermal conductive coating liquid is 30%, the total amount of the thermal conductive filler and polyethylene glycol added accounts for 50% of ethanol, the thermal conductive filler is a mixture of graphene fibers and carbon nanotubes in a molar ratio of 1:1, the average length of the graphene fibers is 15 μm, and the carbon nanotubes are multi-walled carbon nanotubes (MWCNTs) with an outer diameter of 50 nm, an inner diameter of 1.5 nm, and an average length of 20 μm;
[0097] S2, polydimethylsiloxane and hexafluoroacrylate in a mass ratio of 1:1 are stirred and dissolved in ethyl acetate to form a liquid A with a concentration of 10wt%; polyethylene glycol is dissolved in deionized water to form a liquid B with a concentration of 1.5wt%, and liquid A is added dropwise to liquid B at a rate of 0.1mL / min under low-speed stirring at 300rpm at room temperature. After all the additions are completed, stirring is continued for 20min, and the temperature is gradually increased to 40°C at a heating rate of 0.8°C / min in a water bath, and the speed is kept constant and stirring is continued for 2h. Then, the mixture is centrifuged at a speed of 3000rpm at room temperature for 20min, filtered and vacuum dried for 10h, and self-healing microcapsules are obtained after centrifugal filtration and drying, wherein the volume ratio of liquid A to liquid B is 1:5; the capsule wall of the self-healing microcapsule has a thickness of 200-300nm, and the material is polydimethylsiloxane and hexafluoroacrylate, and the material of the capsule core is polyethylene glycol;
[0098] S3, first ultrasonically dispersing the self-repairing microcapsules and silica obtained in step S2 into ethanol respectively, and then adding them into the fluorocarbon resin solution and ultrasonically dispersing them for 60 minutes to obtain a self-repairing hydrophobic coating liquid;
[0099] The volume content of ethanol is 60% of the self-repairing microcapsules and silica, the amount of self-repairing microcapsules added is 20% of the mass of the fluorocarbon resin solution, and the amount of silica added is 5% of the mass of the fluorocarbon resin solution;
[0100] S4, spraying or spin-coating the thermal conductive coating liquid obtained in step S1 uniformly on the surface of the metal substrate, and UV curing for 20 minutes to obtain a thermal conductive coating, wherein the thickness of the thermal conductive coating is controlled to be 50 μm, and the UV curing condition is to use ultraviolet rays with a wavelength of 365 nm and an energy of 5 to 10 J / cm2 for curing;
[0101] S5, continue to evenly spray or spin-coat the self-healing hydrophobic coating liquid prepared in step S3 on the surface of the thermal conductive coating prepared in step S4, and UV cure for 20 minutes to obtain a hydrophobic thermal conductive self-healing coating, wherein the thickness of the self-healing hydrophobic coating is controlled to be 50 μm, and the UV curing condition is to use ultraviolet rays with a wavelength of 365 nm and an energy of 5 to 10 J / cm2 for curing.
[0102] Example 7
[0103] A method for preparing a hydrophobic, thermally conductive, self-repairing coating, the steps are basically the same as those in Example 1, except that in step S2, methyltriethoxysilane and a platinum-based catalyst are added to ethyl acetate while adding polydimethylsiloxane and tetrafluoroethylene, the amount of methyltriethoxysilane added is 1wt% of the polydimethylsiloxane, and the amount of the platinum-based catalyst added is 1wt% of the polydimethylsiloxane.
[0104] Example 8
[0105] A method for preparing a hydrophobic, thermally conductive, self-repairing coating, the steps are basically the same as those in Example 1, except that in step S2, methyltriethoxysilane and a platinum-based catalyst are added to ethyl acetate while adding polydimethylsiloxane and tetrafluoroethylene, the amount of methyltriethoxysilane added is 2wt% of the polydimethylsiloxane, and the amount of the platinum-based catalyst added is 1wt% of the polydimethylsiloxane.
[0106] Example 9
[0107] A method for preparing a hydrophobic, thermally conductive, self-repairing coating, the steps are basically the same as those in Example 1, except that in step S2, methyltriethoxysilane and a platinum-based catalyst are added to ethyl acetate while adding polydimethylsiloxane and tetrafluoroethylene, the amount of methyltriethoxysilane added is 1wt% of the polydimethylsiloxane, and the amount of the platinum-based catalyst added is 0.5wt% of the polydimethylsiloxane.
[0108] Comparative Example 1
[0109] A method for preparing a hydrophobic self-repairing coating, the steps are basically the same as those of Example 1, except that the thermal conductive coating liquid is not prepared, and the self-repairing hydrophobic coating liquid is directly coated on the surface of the metal substrate. The prepared coating is D1.
[0110] Comparative Example 2
[0111] A method for preparing a hydrophobic, thermally conductive, self-repairing coating, the steps are basically the same as those in Example 1, except that in step S1, polyethylene glycol is not added. The prepared coating is D2.
[0112] Comparative Example 3
[0113] A method for preparing a hydrophobic, thermally conductive, self-repairing coating, the steps are basically the same as those in Example 1, except that in step S2, tetrafluoroethylene is not added. The prepared coating is D3.
[0114] Comparative Example 4
[0115] A method for preparing a hydrophobic, thermally conductive, self-repairing coating, the steps are basically the same as those in Example 1, except that in step S3, silicon dioxide is not added. The prepared coating is D4.
[0116] The various properties of the coatings prepared in Examples 1 to 9 and Comparative Examples 1 to 4 were tested, and the test process and results are as follows:
[0117] (I) Weather resistance test
[0118] Including UV aging performance test and heat aging performance test, the test results are shown in Table 1 below.
[0119] Table 1
[0120]
[0121] The UV aging performance was tested using the "GB / T 1865-2009 Artificial Weathering and Artificial Radiation Exposure of Paints and Varnishes to Filtered Xenon Arc Radiation", with a xenon arc lamp as the light source and a wavelength of 340nm and an energy of 0.35W / m 2 The coating was exposed to light for 102 minutes and sprayed with deionized water for 18 minutes, with the light turned off during the spraying period. The cycle was repeated 5 times, and the surface was observed microscopically for cracks and aging. The wear amount was tested using a Taber abrasion tester.
[0122] The wet heat aging performance was tested according to GB / T 23988-2009 Determination of moisture resistance of paints and varnishes. The test temperature was 60±2℃, the humidity was 90±5%, and the test time was 240h.
[0123] As can be seen from the table above, the coatings of Examples 1 to 9 did not blister or crack under UV light and heat and humidity conditions, while Comparative Examples 1 to 4 blister and crack and had low wear resistance. Under the same test environment, the conventional hydrophobic coatings available on the market had obvious blistering and cracking on the surface and poor wear resistance.
[0124] By comparing Example 1 with Comparative Example 1, it can be seen that by combining the thermally conductive coating and the self-healing coating, the thermally conductive coating can effectively conduct heat away under high heat accumulation, thereby greatly improving the weather resistance of the coating.
[0125] By comparing Example 1 and Comparative Example 2, it can be seen that adding polyethylene glycol in step S1 greatly improves the weather resistance of the coating. This is because polyethylene glycol can help to evenly disperse the thermally conductive filler in the epoxy resin solution, prevent filler aggregation, and ensure the uniformity of the coating, thereby improving the thermal conductivity and further improving the weather resistance of the coating.
[0126] By comparing Example 1 and Comparative Example 3, it can be seen that in the process of preparing self-healing microcapsules, by adding fluorine-containing monomers, they can be effectively attached to the surface of the microcapsules, which on the one hand increases the hydrophobicity of the coating, and on the other hand enhances the stability of the microcapsules in high temperature environments, thereby ensuring the durability of weather resistance and self-healing properties.
[0127] By comparing Example 1 and Comparative Example 4, it can be seen that when preparing the self-healing coating, the addition of silica can greatly improve the wear resistance and self-healing performance of the coating. The addition of silica improves the uniform dispersion of the self-healing microcapsules on the one hand, and improves the hydrophobicity and wear resistance of the coating on the other hand, which plays a very important role in improving the resistance of the coating to ultraviolet aging and wet heat aging.
[0128] (II) Scratch self-repair test
[0129] The self-repairing properties of the coatings prepared in Examples 1 to 9 and Comparative Examples 1 to 4 were tested, and the test results are shown in Table 2 below.
[0130] Table 2
[0131]
[0132] The self-healing performance of the coating was tested using the "GB / T 9278-2021 Paint and Varnish Scratch Test". Mechanical scratches were applied to the sample surface. A 5N pencil was used to scratch the sample surface and the scratch depth was controlled to 50 μm. The sample was placed in a standard laboratory environment (25°C, 50% humidity). After 12 hours and 24 hours of scratching, the width and depth of the scratches were observed under a microscope, and the self-healing rate (R s ), the calculation formula is:
[0133]
[0134] Among them, D initial Indicates the initial depth or width of the scratch (when not repaired), D final Indicates the final depth or width of the scratch (after repair), R s Indicates the self-repair rate.
[0135] The above performance test data show that the thermally conductive self-repairing coating of the present invention is superior to conventional coatings in terms of resistance to ultraviolet light aging and moisture and heat resistance, and 24 hours after scratching, the self-repair rate reaches more than 70%, which meets the use requirements and can be widely promoted and used.
Claims
1. A method for preparing a hydrophobic thermally conductive self-repairing coating, characterized in that: The steps include: S1, ultrasonically dispersing a thermally conductive filler and polyethylene glycol in an organic solvent, dripping the mixture into an aqueous epoxy resin solution, and stirring the mixture at a speed of 500 to 1000 rpm for 30 to 60 minutes to obtain a thermally conductive coating liquid; wherein the mass fraction of the thermally conductive filler in the thermally conductive coating liquid is 10 to 30%; S2, dissolving polysiloxane and fluorine-containing monomers in ethyl acetate by stirring to form liquid A; dissolving polyethylene glycol in deionized water to form liquid B, adding the liquid A dropwise to the liquid B under low-speed stirring at room temperature, continuing stirring for 20-30 minutes after all the additions are complete, gradually raising the temperature to 40° C., maintaining the speed constant, continuing stirring for 2-3 hours, and then centrifugally filtering and drying to obtain self-healing microcapsules; S3, adding the self-repairing microcapsules and silica prepared in step S2 to a fluoropolymer solution and / or a hydrophobic resin solution and ultrasonically dispersing for 30 to 60 minutes to prepare a self-repairing hydrophobic coating liquid, wherein the amount of the self-repairing microcapsules added is 10 to 20% of the mass of the fluoropolymer solution and / or the hydrophobic resin solution, and the amount of the silica added is 1 to 5% of the mass of the fluoropolymer solution and / or the hydrophobic resin solution; S4, uniformly spraying or spin-coating the thermal conductive coating liquid obtained in step S1 on the surface of the metal substrate, and UV curing for 10 to 20 minutes to obtain a thermal conductive coating; S5, continue to evenly spray or spin-coat the surface of the thermal conductive coating prepared in step S4 with the self-repairing hydrophobic coating liquid prepared in step S3, and UV cure for 10 to 20 minutes to obtain a hydrophobic thermal conductive self-repairing coating.
2. The method for preparing a hydrophobic thermally conductive self-repairing coating according to claim 1, characterized in that: In step S1, the mass ratio of the thermally conductive filler to the polyethylene glycol is 1:1, the total amount of the thermally conductive filler and the polyethylene glycol added accounts for 30-50% of the organic solvent, the thermally conductive filler is a metal oxide and / or a carbon-based material; the organic solvent is ethanol, isopropanol, benzyl alcohol or ethylene glycol; and the ultrasonic dispersion time is 30-40 minutes.
3. The method for preparing a hydrophobic thermally conductive self-repairing coating according to claim 2, characterized in that: The thermal conductive filler is specifically a mixture of one or more of flaky aluminum oxide nanofibers, flaky zinc oxide nanofibers, graphene fibers or carbon nanotubes. The length of the flaky aluminum oxide nanofibers and flaky zinc oxide nanofibers is 10 to 30 μm.
4. The method for preparing a hydrophobic thermally conductive self-repairing coating according to claim 1, characterized in that: In step S2, the mass ratio of polysiloxane to fluorine-containing monomer in the liquid A is 1:(1-2), the concentration of the liquid A is 5-20wt%, and the concentration of the liquid B is 0.5-2wt%; the volume ratio of the liquid A to the liquid B is 1:(5-10); the dripping rate of the liquid A to the liquid B is 0.1-0.5mL / min; The speed of the low-speed stirring is 300-400rpm; the gradual heating is carried out in the form of water bath heating, and the heating rate is 0.5-0.8°C / min; the centrifugal filtration and drying refers to centrifuging at a speed of 3000-3500rpm for 10-20min in a centrifuge at room temperature, then filtration and vacuum drying for 10-12h, and before vacuum drying, it is repeatedly washed with deionized water for 3-5 times, each time for 3-5min, and a small amount of ethanol is added in the last washing; The capsule wall of the self-repairing microcapsule has a thickness of 200-300 nm, the capsule shell is made of polysiloxane and fluorine-containing monomers, and the capsule core is made of polyethylene glycol.
5. The method for preparing a hydrophobic thermally conductive self-repairing coating according to claim 1, characterized in that: In step S2, a crosslinking agent and a catalyst are added to ethyl acetate while adding polysiloxane and a fluorine-containing monomer. The amount of the crosslinking agent added is 1-2 wt % of the polysiloxane, and the amount of the catalyst added is 0.5-1 wt % of the polysiloxane.
6. The method for preparing a hydrophobic thermally conductive self-repairing coating according to claim 5, characterized in that: The polysiloxane is specifically polydimethylsiloxane or polyvinylsiloxane, the fluorine-containing monomer is tetrafluoroethylene, chlorotrifluoroethylene, vinyl fluoride, vinylidene fluoride or hexafluoroacrylate; the crosslinking agent is methyltriethoxysilane, and the catalyst is a platinum-based catalyst.
7. The method for preparing a hydrophobic thermally conductive self-repairing coating according to claim 1, characterized in that: In step S3, before adding the self-healing microcapsules and the silica to the fluorine-containing polymer solution or the hydrophobic resin solution, the self-healing microcapsules and the silica are first ultrasonically dispersed in ethanol or deionized water, respectively, and the volume content of the ethanol or deionized water is 60-70% of the self-healing microcapsules and the silica.
8. The method for preparing a hydrophobic, thermally conductive, self-repairing coating according to claim 7, characterized in that: The fluorine-containing polymer is polytetrafluoroethylene, polyvinylidene fluoride, fluorine-containing polysiloxane or perfluoroalkyl acrylate copolymer; the hydrophobic resin solution is an organic silicone resin solution, a fluorocarbon resin solution, an epoxy resin solution or a polyurethane resin solution.
9. The method for preparing a hydrophobic thermally conductive self-repairing coating according to claim 1, characterized in that: In steps S4 and S5, the coating thickness is controlled to be 10-50 μm, and the UV curing condition is to use ultraviolet rays with a wavelength of 365 nm and an energy of 5-10 J / cm2 for curing.
10. A hydrophobic, thermally conductive, self-repairing coating prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Cited By
Method for preparing reinforced composite wood floor by adopting low-formaldehyde adhesive
CN120645289A
Epoxy resin / organic silicon composite insulating material with tracking resistance and preparation method of epoxy resin / organic silicon composite insulating material
CN122060287A
Super-amphiphobic coating with repairable function as well as preparation method and application of super-amphiphobic coating
CN122445251A